HNF-1 binding point mutation of the AFP gene promotes cirrhosis in post-menopausal women. Issue 1 (March 2020) - Wang, Jing-wen; Chen, Yong; Liu, Qi-cai; Liu, Guo-zhong; Zhang, Shu-yu; Guo, Yu-jia; Li, Dong-hong; Chen, Xing-ting; Lin, Chen; Gao, Feng
Objective: α-fetoprotein (AFP) expression is activated during the embryonic stage or hepatocellular carcinogenesis, so it is presumed that AFP is a key endogenous molecule to promote cell proliferation or differentiation. We carried out gene screening in an unknown family with hyper-alpha-fetoproteinemia and some sporadic menopausal women, and discussed the relationship between AFP expression and liver cirrhosis. Methods: Peripheral blood samples from family members, patients with malignant liver tumors, and normal controls were collected. Full-length sequence of AFP was amplified and directly sequenced, and compared with normal controls. HNF-1α and HNF-1β in plasma levels of family members, patients with liver cancer, newborns, pregnant women, and normal subjects were detected by ELISA, and the relationship between HNF-1 and AFP mutation or high expression was evaluated. Results: There was a mutation in AFP promoter region at c.-200 C>T, which was located at the binding site of AFP hepatocyte nuclear factor 1 (HNF-1). AFP was higher than 4000 ng/L in all members carrying the mutation, but liver cancer was excluded in the family with hyper-alpha-fetoprotein. However, cirrhosis occurred in post-menopausal women. The cases reviewed showed that unknown hyper-alpha-fetoprotein was closely related to HNF-1 binding point of AFP in post-menopausal women with cirrhosis (7/11), while the plasma levels of HNF-1α and HNF-1β were not significantly different. Conclusion: The mutation of the HNF-1 binding point of AFP may lead to an abnormal high expression of AFP by altering the binding of HNF transcription factors, which is closely related to cirrhosis in menopausal women.